A Longitudinal Investigation of the Relationship between Motivation and Late Second Language Speech Learning in Classroom Settings. (December 2017) - Saito, Kazuya; Dewaele, Jean-Marc; Hanzawa, Keiko
The current study set out to examine the role of learner motivation in second language (L2) speech learning in English-as-a-Foreign-Language classrooms. The motivational orientations of 40 first-year university Japanese students were surveyed via a tailored questionnaire and linked to their spontaneous speech development, elicited via a timed picture description task at the onset and end of one academic semester, in terms of perceived comprehensibility (i.e., ease of understanding) and accentedness (i.e., linguistic nativelikeness). Significant improvement in comprehensibility (but not accentedness) was found among certain individuals. These students likely showed a strong motivation to study English for their future career development as a vague and long-term goal, as well as a high degree of concern for improving comprehensibility, grammatical accuracy and complexity.